Fertilizer Placement and Tillage Interaction in Corn and Soybean Production - A. T. Rosa; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2015)
Different tillage systems can affect the availability of phosphorus (P) by changing the soil environment. The objective of this study was to evaluate the effects and interaction of fertilizer placement, tillage, and varieties for soybean and corn. The experiment was established at two locations in Kansas in 2014. The experimental design was a factorial in a randomized complete block with four replications. Three fertilizer treatments were combined with two tillage systems and two varieties of soybean and corn selected based on contrasting root systems. Plant tissue samples were collected during the vegetative and reproductive stages to evaluate P concentration, P uptake, and dry matter. Significant differences were found in the parameters across locations for corn and soybean. Results suggest advantages for deep-band application for soybean and broadcast application for corn. Varieties responded differently in the parameters evaluated in this study.
Keywords: tillage; corn; soybean; phosphorus; fertilizer placement